Area Not Geographic Isolation Mediates Biodiversity Responses of Alpine Refugia to Climate Change - Huxley, Jared D.; Spasojevic, Marko J. (Frontiers in Ecology and Evolution, 2021)
Climate refugia, where local populations of species can persist through periods of unfavorable regional climate, play a key role in the maintenance of regional biodiversity during times of environmental change. However, the ability of refugia to buffer biodiversity change may be mediated by the landscape context of refugial habitats. Here, we examined how plant communities restricted to refugial sky-islands of alpine tundra in the Colorado Rockies are changing in response to rapid climate change in the region (increased temperature, declining snowpack, and earlier snow melt-out), and if these biodiversity changes are mediated by the area or geographic isolation of the sky-island. We resampled plant communities in 153 plots at 7 sky islands distributed across the Colorado Rockies at two time points separated by 12 years 2007/2008 to 2019/2020) and found changes in taxonomic, phylogenetic, and functional diversity over time. Specifically, we found an increase in species richness, a trend toward increased phylogenetic diversity, a shift toward leaf traits associated with the stress tolerant end of leaf economics spectrum (e.g. lower specific leaf area, higher leaf dry matter content), and a decrease in the functional dispersion of specific leaf area. Importantly, these changes were partially mediated by refugial area but not by geographic isolation suggesting that dispersal from nearby areas of tundra does not play a strong role mediating these changes, while site characteristics associated with larger area (e.g., environmental heterogeneity, larger community size) may be relatively more important. Taken together these results suggest that considering the landscape context (area and geographic isolation) of refugia may be critical for prioritizing the conservation of specific refugia sites that provide the most conservation value.